Trends in Prevalence of Obesity and Overweight Among Children Enrolled in the New York State WIC Program, 2002–2007 - Sekhobo, Jackson P. (Association of Schools of Public Health, 2010)
OBJECTIVE: We examined recent overweight and obesity trends in a multiethnic population of low-income preschool children. METHODS: We defined overweight as sex-specific body mass index (BMI)-for-age ≥85th and <95th percentile and obesity as sex-specific BMI-for-age ≥95th percentile, and calculated them using demographic data and randomly selected height and weight measurements that were recorded while 2- to <5-year-old children were enrolled in the New York State (NYS) Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) during 2002–2007. RESULTS: Obesity prevalence peaked at 16.7% in 2003, declined from 2003 through 2005, and stabilized at 14.7% through 2007. Among both boys and girls, the downward trend in annual prevalence of obesity was evident only among Hispanic children (22.8% boys and 20.9% girls in 2002 vs. 19.3% boys and 17.5% girls in 2007) and non-Hispanic black children (15.6% boys and 14.2% girls in 2002 vs. 13.6% boys and 12.4% girls in 2007). In contrast, the annual prevalence estimate for overweight showed an increasing trend from 2002 through 2007. CONCLUSIONS: These results showed a slight decline in prevalence of childhood obesity and a continuing rise in prevalence of childhood overweight among children enrolled in the NYS WIC program during 2002–2007. Future research should investigate the extent to which the slight decline in childhood obesity prevalence may be attributable to population-based and high-risk obesity prevention efforts in NYS.